Transdermal delivery of somatostatin analogues - Loughman, Thomas Ciarán (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2002)
The aim of this work was to develop transdermal delivery systems for the administration of two peptidic somatostatin analogues, BIM-23014 and its higher potency analogue BIM-23190. Due to its ability to suppress growth hormone and insulin secretion, future therapeutic applications of somatostatin analogues are likely to cover a wide variety of common diseases. Existing dosage forms of these drugs are in the form of parenterals. However, these require supervised administration and are often associated with pain at the injection site and a variable release profile from patient to patient. A transdermal delivery system would necessitate dosing every three days, but patient compliance should increase due to the lack of associated pain and the ability to self-administer the drug. Delivery through the skin eliminates first-pass metabolism thus reducing the dosage necessary to attain therapeutic plasma concentrations and hopefully, side effects. In addition to this, the skin can act as a membrane which effectively controls drug delivery, resulting in close to zero- order delivery and avoidance of peaks and troughs in plasma levels.
Keywords: Pharmaceutics & Pharmaceutical Technology, Ph.D.; Ph.D. Trinity College Dublin